The biological role and immunotherapy of gangliosides and GD3 synthase in cancers - Cao, Shangqi; Hu, Xu; Ren, Shangqing; Wang, Yaohui; Shao, Yanxiang; Wu, Kan; Yang, Zhen; Yang, Weixiao; He, Gu; Li, Xiang (Frontiers in Cell and Developmental Biology, 2023)
Gangliosides are a large subfamily of glycosphingolipids that broadly exist in the nervous system and interact with signaling molecules in the lipid rafts. GD3 and GD2 are two types of disialogangliosides (GDs) that include two sialic acid residues. The expression of GD3 and GD2 in various cancers is mostly upregulated and is involved in tumor proliferation, invasion, metastasis, and immune responses. GD3 synthase (GD3S, ST8SiaI), a subclass of sialyltransferases, regulates the biosynthesis of GD3 and GD2. GD3S is also upregulated in most tumors and plays an important role in the development and progression of tumors. Many clinical trials targeting GD2 are ongoing and various immunotherapy studies targeting gangliosides and GD3S are gradually attracting much interest and attention. This review summarizes the function, molecular mechanisms, and ongoing clinical applications of GD3, GD2, and GD3S in abundant types of tumors, which aims to provide novel targets for future cancer therapy.